Empowering Family Awareness of Cardiovascular Disease in Ngangkrik Hamlet, Sleman Regency - Erinda Nurrahma; Ailsa Nur Rahma Apta Widyadhana; Annisa Leny Saraswati; Ave Anugraheni; Muhammad Jourdan Prasetyatama; Emy Huriyati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Cardiovascular disease is the main cause of death worldwide and in Indonesia. Public awareness and acceptance of preventative cardiovascular care are crucial for reducing illness-related morbidity and mortality. As a result, community service is essential for the primary prevention of cardiovascular disease. Between April and July 2019, this community service was undertaken in Ngangkrik Hamlet, Sleman Regency, Yogyakarta Special Region (DIY). Ngangkrik locals participated in this program in three categories: Bapak Bijak (Wise Dads), Ibu Cerdas (Smart Moms), and Pemuda Bijak (Wise Youngsters). Five stages comprised this program: planning, informing, preparation, implementation, and oversight. Lectures/courses, discussions, practice, and roleplaying were used to implement the materials. To examine participants' knowledge, the pretest and posttest approach was utilized. The program raised participants' knowledge and understanding about the prevention and treatment of cardiovascular disease across all categories.